2000
DOI: 10.1081/cbi-100101032
|View full text |Cite
|
Sign up to set email alerts
|

Day-Night Pattern in Accidental Exposures to Blood-Borne Pathogens Among Medical Students and Residents

Abstract: The purpose of this study was to determine whether the occurrence of accidental blood-borne pathogen exposure incidents in medical students and residents in training varies during the 24 h. A retrospective review of reported exposures was conducted in a large urban teaching institution--the University of Texas Health Science Center in Houston--between November 1993 and July 1998. Professional level (year of student or level of resident), time of exposure, means/route of exposure (needle stick, laceration, or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 16 publications
2
33
0
5
Order By: Relevance
“…14 Substantial decrements in motor performance and a doubling of errors on a laparoscopic surgery simulator task were found in surgical trainees after a 17-hour night work shift without sleep compared with performance after a non-sleep-deprived night. 7 In our study, rates of PI were much greater during nighttime hours than during the daytime in all locations other than the operating room, consistent with data from Parks et al, 2 although in that study, exposure was based on estimated work schedules rather than a validated measure of work hours. As with extended work duration, we found that fatigue was reported more often as a contributing factor for nighttime compared with daytime injuries, and some of the excess in the nighttime rates may be reflecting the effects of extended work shifts.…”
Section: Commentsupporting
confidence: 80%
“…14 Substantial decrements in motor performance and a doubling of errors on a laparoscopic surgery simulator task were found in surgical trainees after a 17-hour night work shift without sleep compared with performance after a non-sleep-deprived night. 7 In our study, rates of PI were much greater during nighttime hours than during the daytime in all locations other than the operating room, consistent with data from Parks et al, 2 although in that study, exposure was based on estimated work schedules rather than a validated measure of work hours. As with extended work duration, we found that fatigue was reported more often as a contributing factor for nighttime compared with daytime injuries, and some of the excess in the nighttime rates may be reflecting the effects of extended work shifts.…”
Section: Commentsupporting
confidence: 80%
“…It is unclear whether the present findings are attributable to the observed admission densities or the increased human-error rates during evening hours, as reported in both medical and nonmedical fields. [30][31][32][33] Nevertheless, it is possible to assess prospectively whether changes in the structure of care, process of care, or a combination thereof could negate the observed differences in mortality rates between daytime and nighttime admissions to the PICU.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding these potential confounders, the results are consistent with previous laboratory and field data. 2,3,16 Pressure to perform procedures quickly, which may vary with time of day and in different specialties, may have contributed to our findings. Operating rooms tend to be busier in the daytime than during the nighttime, which could account for the increased rate of injuries in the operating room in the daytime.…”
Section: Commentmentioning
confidence: 64%